التحكيم في دعوى التطليق للشقاق بين الزوجين "دراسة مقارنة - حاج أحمد, عبد الله (جامعة الوادي University of Eloued, 2015)
ملخص تبحث هذه الصفحات في دور التحكيم في حل النزاعات بين الزوجين، من خلال بيان حكمه، والظروف التي تجعل القاضي يلجأ إليه، وكذا سلطة الحكمين في حل النزاع؛ بتوضيح دورهما الإصلاحي من جهة، ومدى إمكانية حكمهما بالتفريق إذا رأيا فيه المصلحة. وينطلق البحث من بيان مفهوم التحكيم في الشقاق بين الزوجين، ثم كيفية التحكيم في الشقاق بين الزوجين، وأخيرا عمل الحكمين. ABSTRACT: These pages are looking at the role of arbitration in resolving disputes between spouses, Where we address to its religious rule, and the circumstances that render the judge resorted to, As well as the authority of arbitrators in resolving the dispute, clarifying their roles on the one hand, and the extent of the possibility of ruling divorcing if they believe the interest. So we address the concept of arbitration in dissension between spouses, and finally the work of arbitrators.
Arbitration In Divorce Proceedings For Dissension Between The Spouses " A Comparative Study"
Keywords: التحكيم، التطليق، الشقاق بين الزوجين، قانون الأسرة، الفقه الإسلامي